2022
DOI: 10.1007/s11120-022-00979-8
|View full text |Cite
|
Sign up to set email alerts
|

The location of the low-energy states in Lhca1 favors excitation energy transfer to the core in the plant PSI-LHCI supercomplex

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…In previous studies, Zm00001d009589 (lhcb3) was shown to be involved in chloroplast development. Additionally, Zm00001d009589 (lhcb3) and Zm00001d011285 (lhcb10) respond to drought resistance [ 70 , 71 ]. BR can regulate plant growth and drought responses through the WRKY TF family [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Zm00001d009589 (lhcb3) was shown to be involved in chloroplast development. Additionally, Zm00001d009589 (lhcb3) and Zm00001d011285 (lhcb10) respond to drought resistance [ 70 , 71 ]. BR can regulate plant growth and drought responses through the WRKY TF family [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…An example of such renormalization is given in ref. 40, where we model the Lhca1 complex with modified Redfield and compare the results with the complex time-dependent Redfield 50 and HEOM. In the case of LHCII the Redfield-Fo ¨rster and HEOM pictures also require different site energies in order to give correct exciton structures (because of different reorganization shifts of the exciton levels in these two approaches).…”
Section: Equilibration Between the Stromal-side Chls Amentioning
confidence: 99%
“…That is why the Redfield–Förster approach is still more suitable for building the exciton models of antenna complexes. On the other hand, the HEOM solution can be used as a benchmark allowing verification of the obtained models (at least for one realization of the disorder), as was demonstrated in modeling of LHCII, 36 Lhca1, 40 and Lhca4 41 complexes.…”
Section: Introductionmentioning
confidence: 99%
“…LHCII, 46 Lhca4, 47 and Lhca1. 35 It was concluded that both ctR and HEOM give significant (and non-uniform) red-shifting of the exciton transitions as compared to mR. Comparison of the energy transfer kinetics calculated with mR and HEOM 34,46–49 revealed another mR artifact connected to its secular character (the same artifact is also present in the coherent modified Redfield theory (cmR), 50–52 which is also a secular theory including only decay of the initial one-exciton coherences).…”
Section: Introductionmentioning
confidence: 98%
“…In the mR approach the lineshapes are calculated with explicit inclusion of the diagonal exciton-phonon coupling, 27 whereas off-diagonal coupling is accounted for by a phenomenological Markovian term determined by the inverse lifetime of the exciton states (the thus defined term is real and describes a relaxation-induced broadening). 34,35 Besides, more versatile theories of absorption lineshapes have been developed, [36][37][38][39][40][41][42][43] containing non-Markovian generalizations of the modified Redfield lineshapes. Comparison of the absorption spectra calculated with the mR, complex time-dependent Redfield (ctR) theory, 40,42 and nonperturbative hierarchical equation of motion (HEOM) approach 44,45 has been done for model systems 40 and for real antenna complexes from higher plants, i.e.…”
Section: Introductionmentioning
confidence: 99%